2002
DOI: 10.2298/avb0203085s
|View full text |Cite
|
Sign up to set email alerts
|

The plasma levels of triiodothyronine, thyroxine and cortisol in newborn calves

Abstract: The aim 'of this investigation was to determine the concentrations of triiodothyronine (T3), thyroxine (T4) and cortisol in blood plasma from calves during the first 32 h of postnatal life, as well as at 7 days old. The experiment involved two groups of calves. The first group was offered the standard amount of colostrum while the second group received half the recommended amount. The results obtained showed that the calves were born with high plasma concentrations of 73, 74 and cortisol up to four times great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The decrease in the concentration of hormones as time elapses from birth is consistent with that reported for ruminants by other authors (Awadeh et al, 1998;Takahashi et al, 2001;Stojić et al, 2002;Guyot et al, 2011;Rose et al, 2012). In this sense, the highest initial concentration of T3 in the newborn is related to the synthesis of thermogenin, a protein necessary for the production of heat in brown adipose tissue (Carstens, 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The decrease in the concentration of hormones as time elapses from birth is consistent with that reported for ruminants by other authors (Awadeh et al, 1998;Takahashi et al, 2001;Stojić et al, 2002;Guyot et al, 2011;Rose et al, 2012). In this sense, the highest initial concentration of T3 in the newborn is related to the synthesis of thermogenin, a protein necessary for the production of heat in brown adipose tissue (Carstens, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Although it was not possible to find studies conducted under similar conditions, other authors report values of thyroid hormones in the newborn by applying different experimental models that differ from those indicated in this study (Davicco et al, 1982;Stojić et al, 2002;Kirovski et al, 2008). These differences can be attributed not only to factors inherent to the methodologies used for the determination of the hormones but also to the potential influence of the environment on the animals subjected to experimentation.…”
Section: Discussionmentioning
confidence: 51%
“…Cold stimulus after birth has been shown to increase T3 and T4 concentrations [ 26 ]. Stojić et al [ 37 ] reported that different amounts of colostrum consumed by newborn calves had a minor effect on plasma concentrations of T3, T4, and cortisol. Cortisol stimulated by cold stress enhances the maturation of the thyroid axis leading to increased thyroid hormone levels and conversion of T4 to T3 in the BAT [ 16 ].…”
Section: Discussionmentioning
confidence: 99%